First observations of Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) suggest that it is a transient species in Finland - Nissinen, Anne; Latvala, Satu; Lindqvist, Isa; Parikka, Päivi; Kumpula, Raija; Rikala, Kati; Blande, James (Agricultural and Food Science, 2023)
Drosophila suzukii, known as the spotted wing drosophila (SWD), is a major pest of berries and stone fruits. In 2014 it was recorded for the first time in the Nordic countries. In this study, we report the first observations of D. suzukii in Finland. The first trap catches of SWD were observed in 2019 in North Savo at a berry farm that handles imported berries. In 2020–2021, no adult flies were trapped at or near the farm, but in August 2022, adult SWDs were caught at the same farm. In 2023, one female of the same haplotype as the flies in previous year was found in mid July, but no further population growth was observed. This suggests that some overwintering events may happen, but lack of overwintered males may hinder the population growth. In 2021–2022, larvae and eggs of SWD were found in several batches of imported berries. Our results suggest that there is a pathway of introduction for SWD up to the farm level. Observed SWD adults in 2022 probably originated from a new introduction rather than an overwintered population, because no SWDs were observed during the two preceding seasons. Identification of D. suzukii specimens was confirmed with PCR and sequencing of the COI region, and four SWD haplotypes were found.
Keywords: berries; introduction pathways; nvasive pests; PCR; haplotype